Higher division of popliteal artery: a case report - Billakanti, Prakash Babu (International Journal of Research in Medical Sciences, 2017)
During the routine dissection of anatomy in an adult male cadaver at the department of anatomy, Manipal University, Manipal, higher division of popliteal artery was observed on the right side. This artery divided proximal to upper border of popliteus muscle into anterior and posterior tibial arteries. Inferomedial genicular artery which is usually a branch of popliteal artery was found to be arising from anterior tibial artery. However arterial branching pattern and point of bifurcation of popliteal artery on the left side were usual. The knowledge of these variations will be useful for angiography or various surgical approaches during knee joint surgery.